(untitled) (Journal on studies and research of academic knowledge, 2022)
The Electoral Code of the Republic of Paraguay provides legal impediments for those deprived of liberty without conviction to have access to the suffrage, with the referred prohibition, fundamental principles of the National Constitution and the International Covenant on Civil and Political Rights (ICCPR) approved and ratified by Paraguay are violated. The objective of the research was to analyze article 91 inc. "d" of the electoral code contrasting it with the universal principle of the right to vote established in the Paraguayan Constitution and the International Covenant on Civil and Political Rights ratified by the country. The methodology used for this research was the documentary review; the approach was qualitative, the data collection tool was the interview applied in August 2022 to the political actors, electoral judge, representative of the Public Ministry, departmental proxies of the political parties of the National Republican Association and the Authentic Radical Liberal Party in the city of Salto del Guairá. The result was the incompatibility of Art. 91 inc. "d" of the Electoral Code of Paraguay with the universal principle of the right to vote established in the Constitution of the Republic of Paraguay. Therefore, this research concludes this investigation sustaining the existing incompatibility between Art. 91 inc. "d" of the Electoral Code with the universal principle of the right to Suffrage established in the National Constitution of Paraguay and the International Covenant on Civil and Political Rights.